The Social Costs of Sovereign Default - Farah-Yacoub, Juan P.; Graf von Luckner, Clemens; Ramalho, Rita; Reinhart, Carmen (World Bank, Washington, DC, 2022)
This paper estimates the costs of sovereign defaults to a broader extent than has been done in the literature. Applying the synthetic control method to a sample of 131 defaults since 1900, it finds that, on average, growth in the first two years falls 3.6 and 2.4 percentage points short of the counterfactual. Still, after a decade, defaulters’ economic output per capita is nearly 17 percent below that of the counterfactual. Poverty headcounts—available since the 1980s—exceed their pre-crisis levels by roughly 30 percent shortly after default and remain elevated a decade later. Variables proxying access to nutrition, energy, and health outcomes—available since the 1960s—suggest that standards of living decline sharply after sovereign defaults. For instance, on average, by year 10 after default, defaulters have 13 percent more infant deaths every year than the synthetic control. And surviving infants are expected to have shorter lives: life expectancy drops to 1.5 percent below the counterfactual.